2012
DOI: 10.1186/1471-2431-12-70
|View full text |Cite
|
Sign up to set email alerts
|

Measuring transcutaneous bilirubin: a comparative analysis of three devices on a multiracial population

Abstract: Background Hyperbilirubinemia can lead to potentially irreversible bilirubin-induced neurotoxicity. Transcutaneous bilirubin (TcB) determination has become a valuable aid in non invasive screening of neonatal jaundice. The aim of this study is to compare the performance of three most widespread transcutaneous bilirubinometers on a multiracial population of term and late pre-term neonates. Methods Bilirubin concentration was determined using traditional phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 8 publications
4
28
0
Order By: Relevance
“…This study demonstrated a stronger correlation in the Caucasian group compared to the non‐Caucasian group. These findings are consistent with other studies where the correlation between TcB and SBR in non‐Caucasian or darker‐skinned infants is lower than that of Caucasian or lighter‐skinned infants . The trend in agreement is also consistent with other studies in that TcB devices tend to overestimate the SBR measurements (i.e.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study demonstrated a stronger correlation in the Caucasian group compared to the non‐Caucasian group. These findings are consistent with other studies where the correlation between TcB and SBR in non‐Caucasian or darker‐skinned infants is lower than that of Caucasian or lighter‐skinned infants . The trend in agreement is also consistent with other studies in that TcB devices tend to overestimate the SBR measurements (i.e.…”
Section: Discussionsupporting
confidence: 92%
“…positive bias) in non‐Caucasian or darker‐skinned infants (including African American, Thai and Asian sub‐populations) and are less precise than measurements in Caucasian or lighter‐skinned infants where the devices tended to underestimate (i.e. negative bias) …”
Section: Discussionmentioning
confidence: 99%
“…Pearson’s correlation coefficient obtained with Bilistick (r = 0.961) was higher than those reported for any transcutaneous POC instrument that ranged from 0.70 to 0.87 [13,14,15,16,17,18,19,20,21]. The Bland-Altman analysis showed a mean difference between hospital laboratory results and Bilistick determinations of 10.3 µmol/l and a 95% confidence interval of –38.0 to –58.7 µmol/l.…”
Section: Discussionmentioning
confidence: 79%
“…In the past years we developed a skin bilirubin nomogram for the first 96 h of life in a European normal healthy population using BiliCheck™([BC] Respironics, Marietta, GA – USA) and then validated it in a prospective, observational multicenter study [18,22]. BC and JM-103 (Drager Medical Inc, Telford, Pennsylvania) reliability has been evaluated in two recently published papers [23,24]. The purpose of this study was to compare the predictive ability of BiliCheck vs JM-103 in identifying neonates not at risk of significant hyperbilirubinemia, putting the data obtained with the two instruments on our transcutaneous bilirubin nomogram built with the BiliCheck.…”
Section: Introductionmentioning
confidence: 99%